Mississippi John Hurt : his life, his times, his blues - Ratcliffe, Philip R. (American made music series., 2011)
When Mississippi John Hurt (1892-1966) was 'rediscovered' by blues revivalists in 1963, his musicianship and recordings transformed popular notions of pre-war country blues. At seventy-one he moved to Washington, D.C., from Avalon, Mississippi, and became a live-wire connection to a powerful, authentic past. Hurt's intricate and lively style made him the most sought-after musician among the many talents the revival brought to light. This book provides this legendary creator's life story.